Classification and characterisation of magmatic-hydrothermal tourmaline by combining field observations and microanalytical techniques. Issue 1 (July 2020) - Drivenes, K; Brownscombe, W; Larsen, R B; Seltmann, R; Spratt, J; Sørensen, B E
Abstract: Tourmaline from the St. Byron lobe of the Land's End granite, SW England, was assessed by macroscopic, optical and quantitative microanalytical methods. In total, seven types of tourmaline were distinguished. The seven types reflect different crystallisation environments and stages in the magmatic-hydrothermal transition. Types 1-3 are interpreted to represent a gradual transition from tourmaline crystallising from a silicate melt to precipitation from magmatic aqueous fluids. Types 5-7 crystallised at subsolidus conditions from a different fluid generation than types 1-3. These fluids may be magmatic or mixed with other fluids (e.g., meteoric or formation waters). The Sn-mineralisation in the area is mostly related to the latter fluid generation, and the mineralising potential is reflected by the tourmaline composition.